Importance and Comparative Advantages of the EU and US Agri-food Sector in World Trade in 1995-2015 - Karolina Pawlak (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The aim of the paper was to examine the evolution of the importance and comparative advantages of the EU and US agri-food sector in world trade in 1995-2015. The research is based on data from UNCTAD (United Nations Conference on Trade and Development) resources. The following indicators were used in the comparative advantage analysis: Balassa’s Revealed Comparative Advantage (RCA), Vollrath’s Revealed Competitiveness (RC), the Revealed Symmetric Comparative Advantage (RSCA), and the Lafay’s Trade Balance Index (TBI). In 1995-2015, the EU countries and the US were the largest players of world trade in agri-food products. The EU countries held comparative advantages in the global market as regards exports of products of animal origin whereas the exports of cereals, preparations of cereals, oilseeds and oleaginous fruits and meat products were the source of revealed comparative advantages for the US. Both the EU countries and the US reached high comparative advantages in trade in those assortment groups which corresponded to their highest shares in global exports and generated a high, consistently increasing positive trade balance. Therefore, their comparative advantages were the source of their favourable export specialisation profile, which is consistent with the classical comparative costs principle.